2019
DOI: 10.1038/s41586-019-1049-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-scale super-resolved imaging in tissues by RNA seqFISH+

Abstract: Imaging the transcriptome in situ with high accuracy has been a major challenge in single cell biology, particularly hindered by the limits of optical resolution and the density of transcripts in single cells [1][2][3][4][5] . Here, we demonstrate seqFISH+, that can image the mRNAs for 10,000 genes in single cells with high accuracy and sub-diffraction-limit resolution, in the mouse brain cortex, subventricular zone, and the olfactory bulb, using a standard confocal microscope. The transcriptome level profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
1,327
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,338 publications
(1,435 citation statements)
references
References 43 publications
13
1,327
0
3
Order By: Relevance
“…Single‐cell genomics offer powerful tools for unraveling cell heterogeneity in complex organs, the nature of intercellular crosstalk, and disease‐associated cellular reprogramming with unprecedented resolution. New technologies are being developed to further expand single‐cell analysis to include spatial information of cells in their native tissue context, such as sequential FISH and spatially barcoded transcriptomic analysis . In addition, multimodal and integrated methods are available for high‐resolution mapping of chromatin state (DNA methylation, chromatin accessibility, histone modifications), genome sequence, and cell‐surface protein expression in combination with single‐cell transcriptomic analysis, as discussed in a recent review .…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐cell genomics offer powerful tools for unraveling cell heterogeneity in complex organs, the nature of intercellular crosstalk, and disease‐associated cellular reprogramming with unprecedented resolution. New technologies are being developed to further expand single‐cell analysis to include spatial information of cells in their native tissue context, such as sequential FISH and spatially barcoded transcriptomic analysis . In addition, multimodal and integrated methods are available for high‐resolution mapping of chromatin state (DNA methylation, chromatin accessibility, histone modifications), genome sequence, and cell‐surface protein expression in combination with single‐cell transcriptomic analysis, as discussed in a recent review .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…New technologies are being developed to further expand single-cell analysis to include spatial information of cells in their native tissue context, such as sequential FISH and spatially barcoded transcriptomic analysis. (29,30) In addition, multimodal and integrated methods are available for high-resolution mapping of chromatin state (DNA methylation, chromatin accessibility, histone modifications), genome sequence, and cell-surface protein expression in combination with single-cell transcriptomic analysis, as discussed in a recent review. (31) These emerging tools are expected to reveal multidimensional details of the liver microenvironment in physiological and disease states.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To screen which regulatory pathways are affected by cell–cell interactions has been very challenging, a new technology published in the March issue of Nature by Eng et al . points toward a scalable solution . The Improved sequential fluorescence in situ hybridization (SeqFISH+) method allows quantitative gene expression measurements of 10 000 genes in situ within intact tissue samples at single‐cell resolution, within thousands of single cells.…”
mentioning
confidence: 99%
“…This experimental pipeline will, however, not be able to identify which pathways are modulated by local tissue neighborhood. Using their transcriptome‐wide multiplexed single‐molecule fluorescent in situ hybridization method, SeqFISH+, the authors identified without bias a large number of cell types in the mouse cortex and olfactory bulb . From these inferred cell identities, they were able to quantify the degree of colocalization of cell types (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation